Alternative Directions in Art Education and Dissemination of Traditional Arts in a Globalised Society - Santos, Ramon Pagayon (Malaysian Journal of Music, 2016)
The new century bears witness to new developments in the consciousness of peoples around the world, following the colonial experience and the advent of modern education and technological advances. In postmodern discourse in which traditional practices have come to the fore in asserting identity on behalf of individual societies, the transmission of cultural art forms has become an imperative concern among peoples, countries and nations. It is also within this context that the empowerment of traditional artists has been regarded as a necessary tool in the preservation of one’s cultural heritage. This paper discusses the multi-dimensional aspect of transmission and dissemination of traditional practices as part of a process of social evolution and the different participants in the process of learning and disseminating artistic forms of expression, as well as adopting indigenous knowledge in the functioning of contemporary society in Asia and other parts of the globe.